2015
DOI: 10.1016/j.celrep.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Calcium Uniporter Selectively Matches Metabolic Output to Acute Contractile Stress in the Heart

Abstract: SUMMARY In the heart, augmented Ca2+ fluxing drives contractility and ATP generation through mitochondrial Ca2+ loading. Pathologic mitochondrial Ca2+ overload with ischemic injury triggers mitochondrial permeability transition pore (MPTP) opening and cardiomyocyte death. Mitochondrial Ca2+ uptake is primarily mediated by the mitochondrial Ca2+ uniporter (MCU). Here we generated mice with adult and cardiomyocyte-specific deletion of Mcu, which produced mitochondria refractory to acute Ca2+ uptake, augmented AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
362
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(388 citation statements)
references
References 34 publications
22
362
1
3
Order By: Relevance
“…Mitochondria in D7 Des Tg and Ntg hearts were isolated as described previously 22, 23. Briefly, hearts were harvested, homogenized in MS‐EGTA buffer (225 mmol/L mannitol, 75 mmol/L sucrose, 5 mmol/L HEPES, and 1 mmol/L EGTA, pH 7.4) and subjected to differential centrifugation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mitochondria in D7 Des Tg and Ntg hearts were isolated as described previously 22, 23. Briefly, hearts were harvested, homogenized in MS‐EGTA buffer (225 mmol/L mannitol, 75 mmol/L sucrose, 5 mmol/L HEPES, and 1 mmol/L EGTA, pH 7.4) and subjected to differential centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial oxygen consumption rate was measured with an XF24 Extracellular Flux Analyzer (Seahorse Biosciences, North Billerica, MA) by methods as described previously 22, 23, 24. Heart mitochondria were isolated using MS‐EGTA buffer (225 mmol/L mannitol, 75 mmol/L sucrose, 5 mmol/L HEPES, and 1 mmol/L EGTA, pH 7.4) by differential centrifugation as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, additional tests using isolated mitochondria using a physiologically oxidized substrate showed only a modest contribution of Ca 2þ to the in vivo range of respiration [31,32], an observation explained by the finding cardiac function was unaffected in mouse models in which the mitochondrial calcium uniporter was genetically ablated [33,34]. However, conditional tissue-specific cardiac mitochondrial uniporter knockout models by Kwong et al [35] led to a more nuanced picture where exercising mice required a substantial 'warm up time' before being able to exercise at a level similar to control mice and that those changes were associated with changes in calcium content in mitochondria due to adrenergic stimulation. The physiological realism of the Beard mitochondrial C-model was recently revisited by Vinnakota et al [36], who showed that the near equilibrium behaviour of F 1 F O ATPase and the rapid transport of P i from extramitochondrial space to the matrix governed the kinetic feedback from P i to the TCA cycle [36].…”
Section: Isolated Mitochondriamentioning
confidence: 99%